The Impact Of Smartphone Technology On Behavior Of Parents For Aged 40-50 Years: (Case Study: Desa Rawang Baru, Rawang Panca Arga-Asahan Destrict) - Hasanuddin Sirait (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2022)
Good parents' behavior indicates the existence of a personality life from a daily mindset that always leads to positive things, positive behavior from parents can have a very big impact on the survival of family life and social life.In modern times there are many deviations in behavior carried out by people.This times allegedly caused by advances in communication technology, one of which is smartphone technology. It is less able to use the applications contained in Smartphone today such as fb, browsing, listening to music, video players, games, allegedly very influential on the behavior of parents today. That is why the writer feels important to conduct research with the title "The Effect of Smartphone Technology on the Behavior of Parents aged 40-50 years.  Study qualitative methods uses, using a qualitative approach, to explore and describe how much influence smartphone technology on parental behavior. Which is 40-50 years old.The results of this study indicate that smartphone technology can have a significant impact on the behavior of people in Tuminting District, both behaviors that lead to positive things and behaviors that lead to negative things.